2020
DOI: 10.1186/s12957-020-01902-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 17p13 deletion is associated with an aggressive tumor phenotype in clear cell renal cell carcinoma

Abstract: Background: Deletions of 17p13 recurrently occur in renal cell carcinoma (RCC) but their prognostic role seems to be uncertain. Methods: To determine prevalence, relationship with tumor phenotype, and patient prognosis, a tissue microarray containing samples from 1809 RCCs was evaluated using dual labeling fluorescence in situ hybridization (FISH) with 17p13 and chromosome 17 centromere probes. Results: A 17p13 deletion was found in 72 of 1429 interpretable tumors. The frequency of 17p13 deletions varied great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…More specifically, losses in 3p are important for diagnosis and losses in 9p or 14q are important for prognosis. The Cancer Genomics Consortium Workgroup also reported that the TP53 mutation had clinical significance for prognosis, and deletions on 17p13, carrying TP53 , was added as a risk factor because this region is associated with an aggressive tumor phenotype 24,25 . Loss of chromosome 4 is not as well known as losses of chromosome 9 and 14q, but has been reported to be positively correlated with high tumor grade and candidate tumor suppressor genes 26‐28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, losses in 3p are important for diagnosis and losses in 9p or 14q are important for prognosis. The Cancer Genomics Consortium Workgroup also reported that the TP53 mutation had clinical significance for prognosis, and deletions on 17p13, carrying TP53 , was added as a risk factor because this region is associated with an aggressive tumor phenotype 24,25 . Loss of chromosome 4 is not as well known as losses of chromosome 9 and 14q, but has been reported to be positively correlated with high tumor grade and candidate tumor suppressor genes 26‐28 .…”
Section: Discussionmentioning
confidence: 99%
“…The Cancer Genomics Consortium Workgroup also reported that the TP53 mutation had clinical significance for prognosis, and deletions on 17p13, carrying TP53, was added as a risk factor because this region is associated with an aggressive tumor phenotype. 24,25 Loss of chromosome 4 is not as well known as losses of chromosome 9 and 14q, but has been reported to be positively correlated with high tumor grade and candidate tumor suppressor genes. [26][27][28] In our ccRCCs, losses in 3p were detected in 56/60 (93.3%) and 5q gain was detected in 31/60 (51.7%).…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…To thoroughly analyze the potential prognostic value of Napsin A, the subset was separately analyzed at two different antibody dilutions (1:400 and 1:135). This subset of renal cell carcinomas with clinicopathological information has been used in several previously published studies (for example [36][37][38][39][40][41][42]).…”
Section: Prognostic Evaluation Of Napsin a In A Subset Of Renal Cell Carcinomasmentioning
confidence: 99%